Pengaruh Buku Wirid Dzikir Dan Do’a Ud’uuni Astajib Lakum Terhadap Amaliyah Keseharian Santri Ar-Risalah Lubuklinggau - Qomarullah, Muhammad; Kamsi, Nurlila; Nasrian, Ilham; Saputra, Muhammad Ramadhoni; Fernandi, Jerry (Edification Journal : Pendidikan Agama Islam, 2024)
In examining the conditions prevalent in Islamic boarding schools, particularly at Ar-Risalah Lubuk Linggau Junior High School, it is evident that many students exhibit low levels of engagement in their daily amaliyah (such as worship, interpersonal relationships, respect towards teachers and others), and often fail to adhere to Islamic behavioral norms, resulting in less conducive amaliyah among the students. This research endeavors to investigate the impact of the book of dhikr, wirid, and prayers from Astajib Lakum on the daily amaliyah of students at Ar-Risalah Lubuk Linggau Junior High School during the second semester of the 2023/2024 academic year. Employing a quantitative approach with a non-experimental design, the researcher utilized various data collection methods: observation, interviews, questionnaires, and documentation. Data analysis involved compiling and processing gathered information to categorize the influence of the dhikr, wirid, and prayer books into high (14.00%), medium (72.00%), and low (14.00%) categories. The findings indicate that these spiritual practices have a significant influence, with a calculated impact of 0.750 compared to a critical value of 0.532 on the daily amaliyah of the students.